(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
A survey was carried out to investigate culture strategies, disease patterns and mitigations in mono-sex Nile tilapia in Jessore sadar region. Data obtained by questionnaire interview, individual interview, telephonic interview, PRA method, mono-sex Nile tilapia farm survey from four villages. It was observed that 30.769% farmers and farm owner had no training about culture of mono-sex Nile tilapia while 69.230% farmers and farm owner received short term training from different Department of Fisheries, different NGOs. Mono-sex Nile tilapia culture in ponds was basically a three-tier culture system. Pre-stocking management of ponds in the study area comprised dike repairing, aquatic weed control, waste soil removal and undesirable species (predator and trash fish) control. Majority (85%) of the farm owners and farmers depends on ground water and only (15%) depends on surface water. About 95% of farm of farm owners controlled aquatic weeds manually. Removal of predatory and undesired fish from pond used different types of chemicals but most used rotenone (80%). Fertilizer of pond preparation (Organic and inorganic) in the study area but mostly used cases inorganic fertilizers had applied at the rate of urea 114 kg/ha and triple superphosphate 60 kg/ha in 4–5 installments. Stocking density of mono-sex Nile tilapia was 200-380 fry per decimal. It was recorded that 85% of mono-sex Nile tilapia farmers and farm owner applied supplementary such as commercially manufactured feed and 12% are applied of farm made feed. It was observed,they provided heavy fertilizer, high stocking density, over feed provided, provided over dose drugs so ultimated result of disease occured. Parasitic related disease, bacterial diseases, fungal diseases, viral diseases were attacked in mono-sex Nile tilapia. Argulosis and Streptococcus were mostly common disease in this mono-sex Nile tilapia farm. Asian Australas. J. Biosci. Biotechnol. 2018, 3 (3), 190-200